High Serum Adipocyte Fatty Acid Binding Protein Is Associated with Metabolic Syndrome in Patients with Type 2 Diabetes - Jer-Chuan Li; Du-An Wu; Jia-Sian Hou; Yi-Maun Subeq; Hsin-Dean Chen; Bang-Gee Hsu (Journal of Diabetes Research)
Adipocyte fatty acid binding protein (A-FABP) is a key mediator of obesity-related metabolic syndrome (MetS). The aim of this study was to evaluate the relationship between A-FABP concentration and MetS in type 2 diabetes mellitus (DM) patients. Fasting blood samples were obtained from 165 type 2 DM volunteers. MetS and its components were defined using diagnostic criteria from the International Diabetes Federation. Among 165 DM patients, 113 patients (68.5%) had MetS. Diabetic persons who had MetS had significantly higher A-FABP levels (P<0.001) than those without MetS. Female DM persons had higher A-FABP level than man (P<0.001). No statistically significant differences in A-FABP levels were found in use of statin, fibrate, or antidiabetic drugs. Multivariate forward stepwise linear regression analysis revealed that body fat mass (P<0.001), logarithmically transformed creatinine (log-creatinine; P<0.001), female DM patients (P<0.001), and logarithmically transformed high sensitive C-reactive protein (log-hs-CRP; P=0.013) were positively correlated, while albumin (P=0.004) and glomerular filtration rate (GFR; P=0.043) were negatively correlated with serum A-FABP levels in type 2 DM patients. In this study, higher serum A-FABP level was positively associated with MetS in type 2 DM patients.